The comparative studies of gamma-ray shielding properties of the PbO–BaO–B2O3 glass system by using FLUKA code to XCOM program and accessible experimental data. (December 2018) - Mutuwong, C; Nutaro, T; Saiz, A
Abstract: We had performed computer simulations by using FLUKA for investigating the gamma-ray shielding properties of the xPbO-(50-x)BaO-50B2 O3 glass systems for the 356, 662, 1173, and 1330 keV photons (gamma-rays) energies. Then we compared the results to XCOM and the previous experimental published data. We found that the results agree very well with the XCOM and the real data. Furthermore, we also found that the results from FLUKA are closer to the experimental data than the XCOM.